Evaluation of the Implementation of Enterprise Resources Planning on the Quality of Financial Reports at PT. Perkebunan Nusantara XI - Nuri Faiqoti Himmah; Faizal Hadi; Maidatul Karomah; Zakiyah Tur Rohma; Nur Azizah; Ilham Pria Bagus Saputra (Medikun Publisher, 2024)
This research examines the application of the Enterprise Resource Planning (ERP) system in PTPN XI's financial reports. ERP is an integrated software system used to manage various business functions, including finance. The application of ERP to PTPN XI's financial reports aims to increase efficiency, accuracy and reliability in processing and reporting financial information. PTPN XI is a plantation company with high operational complexity. The research results show that the application of ERP to PTPN XI's financial reports provides benefits in the form of process efficiency, reduced errors, and increased accuracy of financial information. However, challenges in implementing ERP include the complexity of data integration and changes in organizational culture. Successful ERP implementation requires thorough preparation, adequate training, and strong management support. The research results show that the application of ERP to PTPN XI's financial reports has provided significant benefits